VALIDITY TEST FOR SHORT GRIT SCALE (GRIT - S) DUCKWORTH ON INDONESIAN MILLENNIALS - Nugroho Dwi Priyohadi; Fendy Suhariadi; Fajrianthi Fajrianthi (Journal of Educational, Health and Community Psychology, 2019)
ABSTRACTÂ This study aims to test the validity and reliability of Grit as a measuring device which was initially developed by Duckworth and Quinn (2009). As commonly known, Grit performs as a research variable in the field of personality psychology, and educational psychology. It is also developed to optimize employeesâ€™ performance in some corporations; hence, it also encompasses the study of industrial and organizational psychology and includes some dimensions of perseverance and passion. Grit Scale has proven to be valid when it tested on military cadets in the USA; however, in order to obtain more validity, it needs to be tested again in Indonesia. Using 200 millennials in Surabaya, Indonesia, as research subjects, this research was conducted between April and July 2019. Confirmatory Factor Analysis (CFA) was performed using Analysis of Structural Moment (AMOS) and proved to be valid. Moreover, Short Grit Scale (Grit-S) was also proven to be valid and reliable with ê“2 = 20.97; probability value = 0.138; RMSEA = 0.045; CFI = 0.972; GFI = 0.976; and AGFI = 0.941. While the composite reliability set was recorded at 0.82. Hence, it is concluded that Short Grit Scale is valid and reliable to be tested on Indonesian millennials.Â Keywords: Grit-S, perseverance, passion, millennials